The proposal of biotic hazard zones in selected spruce dominated regions in Slovakia - T. Hlásny; L. Kulla; I. Barka; M. Turčáni; Z. Sitková; M. Koreň (Journal of Forest Science, 2010)
Biotic agents driven spruce decline has been observed over several regions in Europe. We studied the spatial pattern of spruce stands mortality due to biotic agents in three spruce dominated regions in Slovakia - the Kysuce, Orava and Low Tatras regions. Regularly reported data on sanitary felling were used for the analysis. Geostatistical techniques and other spatial modelling tools were used to design the zones of biotic hazard for each region. Zone A stands for the totally disintegrated stands with extremely elevated activity of biotic agents. Zone B represents the buffer zone around the zone A. Its width depends on the spreading potential of biotic agents and related stand mortality observed during the last years. Zone C stands for the background areas, with more or less healthy stands. Zone-specific forest protection measures are proposed. Such a system allows for the priority rating of unnatural spruce stand conversion and optimal allocation of forest protection measures.